Health Education on Dengue Fever and Early Screening of Non-Communicable Diseases in Coastal Communities, Tarakan City - Ayuk Cucuk Iskandar; Dewy Haryanti Parman; Najihah Najihah; Nanda Halimatussa'diah; Shinta Nur Haliza; Herlina Herlina; Lusiana Lusiana; Vannesa Nur Quraini; Syirah Syirah; Risna Risna (FKM UIN Sumatera Utara Medan, 2026)
Background: Dengue fever remains a major public health concern in Indonesia, particularly in coastal communities where environmental conditions facilitate mosquito breeding. At the same time, the increasing prevalence of non-communicable diseases (NCDs), such as hypertension and diabetes mellitus, underscores the importance of community-based health education and early detection programs. This community service program aimed to improve public knowledge regarding dengue fever prevention and facilitate early screening for NCD risk factors among coastal residents. Methods: A pre–post community intervention was conducted during a one-day community service program in March 2026 in Lingkas Ujung Village, Tarakan City, involving 35 participants. Health education was delivered through interactive sessions consisting of presentations, discussions, and question-and-answer activities supported by posters and standing banners. Participants' knowledge was assessed using pre-test and post-test questionnaires. Health screening included blood pressure, random blood glucose, total cholesterol, and uric acid measurements. Thirty participants completed both the pre-test and post-test, while all 35 participants underwent health screening. Data were analyzed descriptively using mean scores and frequencies. Results: The mean knowledge score increased from 80.7 before the intervention to 97.7 after the educational session. Health screening showed that 48.6% of participants had prehypertension, 34.3% had hypertension, 45.7% had prediabetes, 11.4% had hyperglycemia, 11.4% had elevated cholesterol levels, and 22.9% had elevated uric acid levels. Conclusion: The community service program effectively improved participants' knowledge of dengue fever prevention while facilitating early identification of NCD risk factors. Similar integrated health education and screening programs should be continuously implemented through collaboration among universities, local health authorities, and community organizations to strengthen preventive health efforts in coastal communities.